Determination local geoid Heights Using RTK-DGPS/Leveling and transformation methods - Hussein , Alaa A.; Mahmood, Faleh H. (Iraqi Journal of Science, 2022)
Geodesy is concerned with the relative positioning of points and the gravity field of the earth. For this task, a well-defined coordinate system is needed on which measurements are normally tied to a set of reference points called a geodetic datum (geoid or ellipsoid). The Global Positioning System GPS gives accurately the three-dimensional position of a point (latitude, longitude, and ellipsoidal height) and can measure under all weather conditions. The coordinates of the GPS reference to the World Geodetic System1984 (WGS 84), a global ellipsoid having its origin as the mass center of the earth, and height, referenced to the surface of the ellipsoid . In this research , using RTK-DGPS technique Data collection for study local and leveling, and Earth Gravitational Models (EGM2008,EGM96 ) for determined to geoid undulation utilized 2D polynomial models , and then Using a surface interpolation (kriging) approach, the coordinate and the computed geoidal heights of some well selected points .